INQUIRY LEARNING MODEL AND TEAMS ASSISTED INDIVIDUALIZATION ON PRESSURE MATERIALS TO IMPROVE SCIENCE PROCESS SKILLS AND STUDENT LEARNING OUTCOMES - Juni Angkowati (Universitas Lambung Mangkurat, 2022)
The low level of student process skills in the learning process can have an impact on the level of student understanding which can lead to low student learning mastery. Especially the pressure physics material in class VIII involves a lot of practicum activities. If the activity is omitted and only lecture methods and assignments are given. then students' understanding can be low because the absorption capacity of each student is different. The solution to fix these problems, the teacher applies learning using the inquiry learning model and Teams Assisted Individualization (TAI) to improve teacher activity, student process skills in practicum, and student learning outcomes. This research is classroom action research (CAR) with three cycles. Cycle I and cycle III consisted of two meetings while the second cycle consisted of three meetings. Based on the results of the study, it can be concluded that the teacher's activities in the application of the inquiry learning model and TAI have been carried out by 85.71% in the first cycle, in the second cycle by 92.86, and in the third cycle by 92.86% with a very good category. Practical process skills through the application of inquiry learning models and TAI in the first cycle is 90%, in the second cycle is 97%, and in the third cycle is 98% with a very good category. Student learning outcomes in the first cycle of learning completeness is 84.62%, in the second cycle is 92.31%, and in the third cycle is also 92.31%.Keywords: science process skills, learning outcomes, inquiry, teams assisted individualization. ABSTRAKRendahnya keterampilan proses siswa dalam proses pembelajaran bisa berdampak pada tingkat pemahaman siswa yang dapat menyebabkan rendahnya ketuntasan belajar siswa. Terutama materi fisika tekanan di kelas VIII banyak melibatkan kegiatan praktikum. Apabila kegiatan tersebut dihilangkan dan hanya metode ceramah dan penugasan yang diberikan. maka pemahaman siswa bisa rendah karena daya serap setiap siswa berbeda. Solusi untuk memperbaiki permasalahan tersebut, guru menerapkan pembelajaran dengan menggunakan model pembelajaran inkuiri dan Teams Assisted Individualization (TAI) untuk meningkatkan aktivitas guru, keterampilan proses siswa dalam praktikum, dan hasil belajar siswa. Penelitian yang dilakukan adalah penelitian tindakan kelas (PTK) dengan tiga siklus. Siklus I dan siklus III terdiri dari dua pertemuan sedangkan siklus II terdiri dari tiga pertemuan. Berdasarkan hasil penelitian dapat disimpulkan bahwa aktivitas guru dalam penerapan model pembelajaran inkuiri dan TAI sudah terlaksana sebesar 85,71% pada siklus I, pada siklus II sebesar 92,86, dan pada siklus III sebesar 92,86% dengan kategori sangat baik. Keterampilan proses praktikum melalui penerapan model pembelajaran inkuiri dan TAI pada siklus I sebesar 90%, siklus II sebesar 97%, dan pada siklus III sebesar 98% dengan kategori sangat baik. Hasil belajar siswa pada siklus I ketuntasan belajar sebesar 84,62%, pada siklus II sebesar 92,31%, dan pada siklus III juga sebesar 92,31%.Kata kunci: keterampilan proses sains, hasil belajar, inkuiri, teams assisted tndividualization.